Gender equity in eye health of Nepal: A hospital-based study - Shrestha, M K; Chan, H; Gurung, R (Nepalese Journal of Ophthalmology, 2012)
Introduction: There is a lack of literature examining the impact of gender on access to eye care in developing countries. Objective: To assess the differences in access to eye care between females and males, in the urban hospital setting and in rural outreach clinics. Materials and methods: A retrospective study was designed to review the patients who sought eye care at a tertiary level eye care institute and its rural outreach clinics from 2006 to 2009 in Nepal. Data were retrieved from clinical records. Results: In the hospital, females accounted for 50.8% of patients receiving outpatient care and 48.3% of patients receiving surgical care. In rural outreach clinics, females accounted for 56.1% of clinic patients and 51.5% of patients undergoing surgery. Fewer girls than boys aged 0-14 years (44.3%) sought clinical care at the hospital. Conclusion: Females account for approximately half of the hospital eye care services in Nepal. More females seek care at rural outreach clinics than at the urban hospital. However, given the female burden of disease in Nepal, there is still much improvement to be made in this area of care.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6544 Nepal J Ophthalmol 2012; 4 (2): 277-281